GAGA Factor Expedites Development in Drosophila - Paromita Das; Manika Pal Bhadra; Utpal Bhadra (Open Journal of Biological Sciences - Peertechz Publications, 2017)
The development in Drosophila is a concerted mechanism, occurring via the interplay of a constellation of genes and factors, operating in intricate synchrony. These factors, produced at precise points in their developmental cycle, operate via the activation, through binding to the various transcription factors. The GAGA factor (GAF) is such a product of the trithorax-like gene, Trl, which binds to a consensus DNA sequence for the modulation of the homeotic gene functions. Besides this, the factor has a role in chromatin remodelling; through binding with the Polycomb responsive element (PRE). The protein has a unique structural conformation with a zinc-fi nger DNA-binding, a BTB/POZ and a polyglutamine-rich Q domain. It has a unique role of acting as an anti-repressor of the gene, Kruppel, releasing the repression on it by the other DNA binding proteins. This report accomodates the interplay in which the GAGA factor is involved in the Drosophila embryonic development.